An Analysis Of Commmunity Satisfaction Index Of Public Services Of The Hajj And Umrah Organizing Section Of The Ministry Of Religion Office In South Bengkulu Regency - Miki Asrayani; Ida Anggriani; Abdul Rahman (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
This study aims to measure how high the level of community satisfaction is with public services in the Hajj and Umrah Organizing Section of the Ministry of Religion Office in South Bengkulu Regency. Collecting data by distributing questionnaires. The data analysis technique used is to measure the value of CSI based on the Regulation of the Minister of Administrative Reform and Bureaucratic Reform Number 14 of 2017. The results of the CSI in the Hajj and Umrah Organizing Section of the Ministry of Religion of South Bengkulu Regency as a whole obtained an CSI score of 88.14 with service quality B and the performance assessment of the service unit was Good in the value interval of 76.61-88.30. This illustrates that the services provided by the Hajj and Umrah Organizing Section of the Ministry of Religion Office in South Bengkulu Regency are good and provide satisfaction to the community. Element U1 (requirements) with a value of 3.926 in the very good category. Element (U8) regarding Handling, Complaints, Suggestions and Feedback received the lowest rating of all elements of CSI. This is because there has been no direct attention the Ministry of Religion Office in South Bengkulu Regency to complaints felt by the community. If the community has complaints about services, it is difficult for the community to provide suggestions and criticisms because there is no suggestion box available so that the response given by the Ministry of Religion Office in South Bengkulu Regency to these community complaints is still considered unsatisfactory.